Standard score for physical tests and their relationship to the achievement of two activities of 100 m and weight throwing for first-level students of the College of Physical Education and Sports Sciences for women - حوراء فلاح جلوب أ.م.د أيمان صبيح (physical education and sport sciences college for women/ Baghdad University, 2021)
The College of Physical Education and Sports Sciences for women  is one of the colleges that are accepted through admission tests, which are a group of tests that the advanced student undergoes and that the student's success in the tests depends on strength and speed as well as strength of will and there are specifications that the student must be distinguished by such as length, mass and compatibility And the athletics lesson is one of the important lessons in the colleges of physical education and the practical lessons in the first course for students of the College of Physical Education and Sports Sciences for women, and there is a link between activities and physical tests for female students 'admission and the research aims to identify the standard score for physical tests with the achievement of the effectiveness of the 100 m for students of the level and identifying the relationship of the standard score for physical examinations with the effectiveness of weight ejection for first-level students. It is assumed that there is a statistical indication between the standard score for the physical tests for first-level students and the existence of a statistically significant relationship between the standard score for the tests and the ejection of weight for the first-level students. Research and be a search community (92) female students. As for the research sample, it is made up of all students of the level admitted to the College of Physical Education and Sports Sciences for girls, whose number is (92) female students, where all data are completed and filled out in forms. A significant correlation relationship was concluded between the standard score of the physical exams for admission with the achievement of 100 m and the ejection of weight, and the study reached that . It is necessary to use he level of skill performance for all games in the College of Physical Education and Sports Sciences for women.